The Effect of Human Resources Development on the Work Effectiveness of Employees of the Muara Enim Regency Cooperative, Small and Medium Enterprises Office - Evi Sulaini; Hardiyansyah Hardiyansyah; Nisma Aprini (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
This study aims to find out and analyze whether there is an influence of human resource development on the work effectiveness of employees of the Office of Cooperatives, Small and Medium Enterprises of Muara Enim Regency and to find out and analyze whether there is a positive and significant relationship between human resource development and work effectiveness of employees of the Office of Cooperatives , Small and Medium Enterprises Muara Enim Regency. The sample in this study were all employees of the Office of Cooperatives, Small and Medium Enterprises, Muara Enim Regency, totaling 32 people. So the sampling technique used in this study using saturated sampling method. Sampling is saturated, namely the technique of determining the sample if all members of the population will be sampled in research or can also be called a census in a small scope. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Data analysis techniques using validity test, reliability test, normality test. The analysis used was descriptive analysis and inferential analysis using statistical calculations with a simple linear regression formula, coefficient of Cooperatives, Small and Medium Enterprises of Muara Enim Regency. The results of the analysis show that human resource development has a fairly strong contribution to the work effectiveness of the employees of the Office of Cooperatives, Small and Medium Enterprises, Muara Enim Regency.